Conceptual art and its role in awareness campaigns - Ali Adel Fouad; Bahaa Abdul Hussein Majeed (Basrah Arts Journal, 2023)
Conceptual or conceptual art considers the idea to be the machine that produces art, and the plan becomes by using artistic tools such as line, space, color, simile and etaphor in the service of the idea communicating with the recipient in an nteresting and non-traditional way and can attract the recipient and provoke his thinking and support the message contained in the design of the idea, so conceptual art played a role Important in these campaigns, through the idea, the art was able to transform the advertisement into a visual image with two dimensions that attracts the mind and arouses attention. Accordingly, the structure of the study was established in four chapters, in which the first chapter (the methodological framework of the research) came from the research problem, which is summarized in the following question : What are the basic steps required for the success of awareness campaigns? The importance of the research and the need for it, and the aim of the research, were determined by defining the intellectual dimension of conceptual art, the objective and temporal limits of research, and the spatial limits, then defining and defining the terms. The role of conceptual art in educating the community) and then came the third chapter (research procedures) and the researcher identified the research community consisting of approximately (17) works of art.